PEMETAAN KEKUATAAN DAN TANTANGAN DESA WISATA PANCASILA JRAHI: PENDEKATAN SWOT UNTUK PENGEMBANGAN BERKELANJUTAN - Prasetiyo, Muhammad Jodi; M. Nur, Dany Miftah; Wahayuningtiyas, Ainun (Sosial Khatulistiwa: Jurnal Pendidikan IPS, 2025)
The purpose of this study was to determine the extent of development that has been carried out by tourism managers and what strategies are suitable for developing the Pancasila Jrahi Tourism Village. This research is a field research (field research) in which researchers go directly to the field to collect the necessary data and information. The method used is a qualitative method using SWOT analysis to see strategies that can be used in the development of the pancasila jrahi tourist village. The results of this study are several alternative strategies that can be applied in its development related to 4 aspects of development strategies, namely destination aspects, industrial aspects, marketing / marketing aspects, and institutional / HR aspects. a) strategy of branding the tourism destination of Pancasila Jrahi Village. b) strategy of building good and attractive accessibility to tourist attractions. c) strategies to create a beautiful and attractive atmosphere in the tourist environment. d) strategies to increase tourism product certification. e) strategies to develop tourism products based on the characteristics/uniqueness of local potential. f) strategies to increase marketing activities for local tourism products.